EP873 Thinking ouside the box- hyperthecosis in postmenpause. (1st November 2019) - Ibrahim, E
Abstract : Introduction/Background: Ovarian hyperthecosis is a rare form of tumour. Women present with hyperandrogenism and virilisation. Affecting postmenpause women mainly <1% and rarely premenopausal women. Ovarian hyperthecosis refer to the presence of luteinized thecal cells within the ovarian stroma, separate from the follicles, and is accompanied by a moderate degree of stromal hyperplasia. The luteinized thecal cells may occur as single cells, small nests, or occasionally nodules. The ovary produces and releases androgens, including 20% of DHEA, 50% of androstenedione and 25% of circulating testosterone. elevated serum testosterone level provides biochemical evidence of hyperandrogenism. Marked high testosterone levels are an indication to investigate androgen secreting tumor. Methodology: Case report of 67-year-old referred from the endocrine clinic. Presented with ongoing hirsutism since around the menopause. Results: All bloods normal. MRI - normal ovaries and adrenal glands. Thick endometrium 6 mm. Discussion with patient about benefit of oophorectomy in the absence of obvious source of excess androgens. Pt had laparoscopic bilateral salpingoophrectomy and hysteroscopy D&C. Procedure was uneventful. Intraop finding- normal anteverted uterus. Endometrium unremarkable. Right ovary slightly enlarged. Conclusion: The cause of ovarian hyperthecosis is still unknown but there are several factors involved including genetics. Our patient mother had hirsutism which support this theory. Usually there would be biochemical and radiological evidence pointing to the source of the tumour. In our case though the ovaries looked normal in MRI.the histopathology was positive for bilateral ovarian hyperthecosis. This indicate that negative imaging is not an strong negative predictive test. Disclosure: Nothing to disclose.